2012
DOI: 10.1177/0961203312439640
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that abnormally large seasonal declines in vitamin D status may trigger SLE flare in non-African Americans

Abstract: Cross-sectional studies have shown that low vitamin D (25-hydroxyvitamin D (25(OH)D)) is associated with increased systemic lupus erythematosus (SLE) activity. This study is the first to assess the temporal relationship between 25(OH)D levels and onset of SLE flare. This assessment was made possible because of the specimen bank and database of the Ohio SLE Study (OSS), a longitudinal study of frequently relapsing SLE that involved regular bimonthly patient follow-up. We identified for this study 82 flares from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 54 publications
(71 reference statements)
1
42
0
1
Order By: Relevance
“…7,9,14,16,38 In contrast, there were reports that lower serum 25(OH)D levels were associated with higher disease activity 10,15,17,22,23 and flares of lupus activity. 24,25 In our study, the disease activity and damage were generally low. We excluded patients who were hospitalized 1 month before their visits because it might limit the sun exposure and effect on serum 25(OH)D levels.…”
Section: Discussionmentioning
confidence: 83%
“…7,9,14,16,38 In contrast, there were reports that lower serum 25(OH)D levels were associated with higher disease activity 10,15,17,22,23 and flares of lupus activity. 24,25 In our study, the disease activity and damage were generally low. We excluded patients who were hospitalized 1 month before their visits because it might limit the sun exposure and effect on serum 25(OH)D levels.…”
Section: Discussionmentioning
confidence: 83%
“…22 A recent study showed that seasonal declines in vitamin D levels may trigger flares in non-African American SLE patients. 51 Contrarily, four studies in adult lupus showed no association between vitamin D levels and lupus activity. [23][24][25][26] These controversial findings may be explained by the limited number of patients analyzed and differences in the severity of disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…LN flares were documented on the basis of criteria for proteinuria, serum creatinine, and urine sediment ( Table 2) that closely parallel the current ACR criteria for LN flare, which we have previously detailed (3)(4)(5)(6). Proteinuria was quantified as protein-to-creatinine ratios from intended 24-hour urine collections.…”
Section: Ln Flare Adjudicationmentioning
confidence: 99%